Lyding - Fredrika de Villiers (AOSIS, 1985)
Suffering as a concept lies beyond man's understanding although its experience is very real. Man may experience physical, psychological or spiritual suffering. A person can adapt to suffering negatively which may lead to complete psychological break-down. A positive attitude towards suffering implies accepting it and believing that it has a purpose. Suffering may then lead to spiritual growth and self-actualisation. The nurse's role in supporting the suffering in thus to help the person to experience it positively and to use it constructively. This requires special skill, sensitivity and a strong faith.